2007
DOI: 10.1227/01.neu.0000249207.66225.d9
|View full text |Cite
|
Sign up to set email alerts
|

Three-Day Phenytoin Prophylaxis Is Adequate After Subarachnoid Hemorrhage

Abstract: A 3-day regimen of PHT prophylaxis is adequate to prevent seizures in subarachnoid hemorrhage patients. Drug reactions are significantly reduced, but seizure rates do not change. Short-term PHT administration may be a superior treatment paradigm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 25 publications
2
42
0
Order By: Relevance
“…In other series, effect of AEDs medication on prevention of late epilepsy was unclear 17,23,24) . These data were similar to those noted for patients with traumatic closed head injury in whom early AED use did not change the incidence of delayed epilepsy 6,10,28,31) .…”
Section: General Overviewsupporting
confidence: 83%
“…In other series, effect of AEDs medication on prevention of late epilepsy was unclear 17,23,24) . These data were similar to those noted for patients with traumatic closed head injury in whom early AED use did not change the incidence of delayed epilepsy 6,10,28,31) .…”
Section: General Overviewsupporting
confidence: 83%
“…Table 3 These data suggest that the effect of prophylactic PHT may be analogous to subarachnoid hemorrhage in terms of increased fever and worse functional outcomes. 9,10 More patients received prophylactic PHT than had seizures clinically or on EEG monitoring, suggesting that clinicians were more concerned with seizures than potential toxicity from PHT.…”
Section: Discussionmentioning
confidence: 99%
“…8 Increased PHT exposure, however, is associated with worse cognitive and functional outcomes after subarachnoid hemorrhage 9 with fewer side effects after 3 compared with 14 days of prophylaxis. 10 Preventing seizures after ICH may not improve outcomes because seizures may not be independently associated with worse outcomes after adjustment for other predictors. 4,11 Additionally, AED use (especially PHT) might be associated with fever, and fever is associated with worse outcomes after ICH.…”
mentioning
confidence: 99%
“…After this initial period the incidence of seizures is low [18]. Chumnavej et al demonstrated that a 3-day regimen of phenytoin prophylaxis is safer and equally effective in comparison with arbitrary longer-term phenytoin coverage, as the incidence of significant side effects is greatly reduced without a concomitant increase in the risk of seizures, even if 80% of patients received aneurysm repair by craniotomy [22]. This data is consistent with that of traumatic head injury patients in whom early anticonvulsant use did not change the incidence of late seizures.…”
Section: Anticonvulsants For Subarachnoid Hemorrhagesmentioning
confidence: 99%